Exploring the sequence diversity and surface expression of Factor H-Binding Protein among invasive serogroup B meningococcal strains from selected European countries - Stephen A. Clark; Laura Willerton; Heike Claus; Anna Carannante; Paola Stefanelli; Raquel Abad; Julio A. Vázquez; Ray Borrow (Taylor & Francis Group, 2024)
Factor H-Binding Protein (fHbp) is a key component of meningococcal vaccines such as MenB-fHbp, licensed in the EU, UK, and other countries. Sufficient expression of fHbp on the bacterial surface is necessary for vaccine-induced antibodies to bind and exert bactericidal activity. The flow cytometric MEASURE assay quantifies fHbp expression in vitro, and previous studies have shown that strains with a Mean Fluorescence Intensity (MFI) >1000 are likely to be killed by MenB-fHbp-induced antibodies. This study assessed fHbp peptide distribution and expression among 451 invasive group B strains collected in 2016 across England, Wales, and Northern Ireland (EW&NI), Germany, Italy, and Spain. We found that 92% of the strains expressed fHbp above the MFI 1000 threshold. The strain distribution across EW&NI, Germany, and Italy was similar, with coverage ranging from 92.1% to 94.6%, dominated by a small number of clonal complexes and fHbp peptides. Although, the Spanish subset had a higher proportion of lower-expressing strains, particularly clonal complex 213, resulting in a lower predicted coverage for Spain (84%). These results, along with other published MEASURE data, can provide a basis for genotypic MenB-fHbp coverage predictions, however, inclusion of the upstream intergenic sequence of the fHbp gene in the prediction improved its accuracy by distinguishing between low- and high-expressing strains. Future MEASURE analyses of strains with less common fHbp variants would serve to further refine vaccine coverage predictions.